Halogen bonding as a supramolecular dynamics catalyst - Szell, Patrick M. J. (Nat Commun, 2019)
Dynamic processes have many implications in functional molecules, including catalysts, enzymes, host-guest complexes, and molecular machines. Here, we demonstrate via deuterium NMR relaxation experiments how halogen bonding directly impacts the dynamics in solid 2,3,5,6-tetramethylpyrazine cocrystals, catalyzing the methyl group rotation. On average, we observe a reduction of 56% in the rotational activation energy of the methyl groups in the halogen bonded cocrystals, contrasting the reduction of 36% in the hydrogen bonded cocrystals, with respect to pure 2,3,5,6-tetramethylpyrazine. Density functional theory calculations attribute this superior catalytic ability of the halogen bond to the simultaneous destabilization of the staggered conformation and stabilization of the gauche conformation, overall reducing the rotational energy barrier. Furthermore, the calculations suggest that the catalytic ability of the halogen bond may be tuneable, with stronger halogen bond donors acting as superior dynamics catalysts. Thus, halogen bonding may play a role in both assembly and promoting dynamical processes.